Accounting Training with the Topics of Accounting Basics for Students of SMP Bunga Bangsa 4 Medan: Pelatihan Akuntansi Dengan Topik Dasar-Dasar Akuntansi Bagi Siswa SMP Bunga Bangsa 4 Medan - Limbong, Christine Herawati; Hanum, Fauziah; Sufritayati, Sufritayati; Zahara, Zahara (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
This training and community service activity was carried out for students of SMP Bunga Bangsa 4 Medan which was held on January 20, 2023. This training took place in the hall room of SMP Bunga Bangsa 4 Medan. Participants who took part in this accounting training numbered around 37 students, who were also attended by students, as well as accounting lecturers at Labuhanbatu University Economics Study Program, Department of Accounting. This training and community service activity went well and smoothly as planned, this can be seen from the enthusiasm and enthusiasm of the students who took part in the training. The purpose of conducting training and research is to provide socialization about the science of accounting that is fun, where so far there has been an assumption that accounting is a science that is a little more difficult to understand. With this training it is hoped that students of SMP Bunga Bangsa 4 Medan, later when dividing majors at SMA (High School) or when graduating from school can choose the Accounting major as their choice when studying in the future. This training and community service method is carried out by conducting material presentations, discussions with students participating in the training, and also practicing simple accounting cycles so that they can attract the interest of students participating in the training. Abstrak Kegiatan pelatihan dan pengabdian masyarakat ini dilakukan bagi siswa/i SMP Bunga Bangsa 4 Medan yang dilaksanakan pada 20 Januari 2023. Pelatihan ini berlangsung di ruangan aula SMP Bunga Bangsa 4 Medan. Peserta yang mengikuti pelatihan akuntansi ini berjumlah sekitar 37 orang siswa/i, yang diikuti juga oleh mahasiswa, serta dosen akuntansi Universitas Labuhanbatu Program Studi Ekonomi Jurusan Akuntansi. Kegiatan pelatihan dan pengabdian masyarakat ini berjalan dengan baik dan lancar sesuai dengan yang direncanakan, hal ini terlihat dari antusias dan semangat siswa/i yang mengikuti pelatihan. Tujuan dilakukannya pelatihan dan penelitian adalah memberikan sosialisasi tentang ilmu akuntansi yang menyenangkan, dimana selama ini timbul anggapan bahwa akuntansi merupakan ilmu sedikit lebih sulit dipahami. Dengan adanya pelatihan ini diharapkan agar siswa/i SMP Bunga Bangsa 4 Medan, nantinya ketika pembagian jurusan pada saat SMA (Sekolah Menegah Atas) ataupun ketika lulus dari sekolah dapat memilih jurusan Akuntansi sebagai pilihannya ketika kuliah dimasa mendatang. Metode pelatihan dan pengabdian kepada masyarakat ini adalah dilakukan dengan melakukan pemaparan materi, diskusi dengan siswa/i peserta pelatihan, dan juga mempraktikkan siklus akuntansi sederhana agar dapat menarik minat siswa/i peserta pelatihan.